Plan de comunicación interna para la empresa logística PerúInterCargo (PIC) - Reyes Vicuña, Mayra Alejandra (2021)
PeruInterCargo (PIC) is one of the three most important logistics operators in Peru and has more than 40 years of service. PIC currently faces the lack of commitment from the leaders of each team with respect to the organizational culture and the consequent loss of talent. This paper proposes to develop an internal communication plan in two phases: the first aimed at all PeruInterCargo leaders in order to improve the behavior and role of the leader, the second phase aimed at all workers to reinforce the corporate culture. The main objective of the plan is to enhance employee engagement through corporate culture and various actions that include the execution of programs and cultural experiences that will allow for the recovery of organizational commitment.